PENGARUH RASIO PERTUMBUHAN PREMI DAN RASIO BEBAN KLAIM TERHADAP TINGKAT KESEHATAN PERUSAHAAN ASURANSI DI MASA PANDEMI COVID-19 - Melisa Anggraini; Wulandari; Bonaventura Hendrawan Maranata; Febe Tri Sinta Dewi (Fakultas Ekonomi dan Bisnis, 2022)
Pandemic of Covid-19 makes people increase the awareness of insurance in their daily lives. This increase in awareness has led to the importance of insurance companies that have a good level of health and their performance can be assessed by the public. Performance in insurance companies can be reflected in a system called the Early Warning System. Meanwhile, the health level of the insurance company is reflected in Risk Based Capital. The Early Warning System consists of several ratios, including the premium growth ratio and claim expense ratio This study aims to test whether the premium growth ratio and claim expense ratio affect the health level of the insurance company. The health level of the insurance company is proxied with Risk Based Capital (RBC). The population used in this study were insurance companies listed on the Indonesia Stock Exchange from the 2020-2021 period. The sample selection method used is purposive sampling. The hypothesis testing of the research used is multiple regression analysis using the eviews program. The result of this study is that there is no influence between the premium growth ratio and the health level of the insurance company and there is an influence between the claim expenses ratio and the health level of the insurance company.